MANAJEMEN KEPALA SEKOLAH DALAM PENINGKATAN KOMPETENSI PROFESIONAL BERBASIS TEKNOLOGI DI TK NEGERI PEMBINA KECAMATAN DEMAK - Ima Dwi Rosadi; Endang Wuryandini; I Made Sudana (Universitas Negeri Malang, 2025)
Abstract: Wise use of technology by principals can help facilitate the improvement of teacher competency. Principal management and teacher professional competency are interconnected because they influence each other. Therefore, the role of the principal as an educator is expected to be a figure who strives for change for teachers so that they consistently carry out their teaching duties optimally.The purpose of this study is to describe the planning, organization, implementation, and supervision of technology-based professional competency improvement for teachers at Pembina State Kindergarten in Demak District. This study is a qualitative descriptive study. The subjects were the principal and seven teachers at Pembina State Kindergarten in Demak District. Data were collected through interviews, observation, and documentation. Data analysis included data collection, data reduction, data presentation, and drawing conclusions.Technology-based professional competencies in teachers are: a) identifying problems and analyzing needs; b) Setting goals; c) Preparing programs and strategies and d) Preparing budgets. 2) Organizing the principal in improving technology-based professional competencies in teachers includes: a) Team formation and division of tasks; b) Internal coordination; c) Resource management. 3) Implementation of the principal in improving technology-based professional competencies in teachers is: a) Program implementation; b) Facilitation and support; and c) Direct monitoring. 4) Supervision of the principal in improving technology-based professional competencies in teachers at TK Negeri Pembina, Demak sub-district is: a) Implementation of supervision; and b) Evaluation and follow-up. Keywords: principal management, professional competence, technology Abstrak: Pemanfaatan teknologi secara bijak oleh kepala sekolah dapat membantu memudahkan dalam meningkatkan kompetensi guru. Manajemen kepala sekolah dan kompetensi professional guru saling berkaitan karena saling mempengaruhi satu sama lain. Oleh karena itu, peran pemimpin selaku Kepala Sekolah sebagai educator diharapkan menjadi sosok mengupayakan perubahan bagi para guru agar senantiasa menjalankan tugas pembelajarannya secara maksimal. Tujuan penelitian ini mendeskripsikan perencanaan, pengorganisasian, pelaksanaan dan pengawasan dalam meningkatkan kompetensi profesional berbasis teknologi pada guru di TK Negeri Pembina Kecamatan Demak. Penelitian merupakan penelitian deskriptif kualitatif. Subyek penelitian adalah kepala sekolah, guru yang ada di TK Negeri Pembina Kecamatan Demak yang berjumlah 7 orang. Pengumpulan data melalui wawancara, observasi dan dokumentasi. Analisis data meliputi pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan: 1) Perencanaan kepala sekolah dalam meningkatkan kompetensi professional berbasis teknologi pada guru adalah: a) mengidentifikasi masalah dan menganalisis kebutuhan; b) Menetapkan Tujuan; c) Penyusunan program dan strategi dan d) Penyusunan anggaran. 2) Pengorganisasian kepala sekolah dalam meningkatkan kompetensi professional berbasis teknologi pada guru diantaranya adalah: a) Pembentukan tim dan pembagian tugas; b) Koordinasi internal; c) Pengelolaan sumber daya. 3) Pelaksanaan kepala sekolah dalam meningkatkan kompetensi professional berbasis teknologi pada guru adalah: a) Implementasi program; b) Fasilitasi dan dukungan; dan c) Pemantauan langsung. 4) Pengawasan kepala sekolah dalam meningkatkan kompetensi professional berbasis teknologi pada guru di TK Negeri Pembina kecamatan Demak adalah: a) Pelaksanaan pengawasan; dan b) Evaluasi dan tindak lanjut. Kata Kunci: manajemen kepala sekolah, kompetensi professional, teknologi